1963
DOI: 10.1017/s0007485300048823
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental conditions on the contact toxicity of some insecticide deposits to adult mosquitos, Anopheles stephensi List

Abstract: Investigations have been made on the influence of environmental conditions on the contact toxicity to adult mosquitos (Anopheles stephensi List.) of two kinds of insecticidal deposits of importance in sprayed houses, superficial deposits from wettable powders and insecticides sorbed on dried soils.Increasing the relative humidity from 43 to 80 per cent, during the contact period had no effect on the toxicity of wettable-powder deposits on plywood of dieldrin, Sevin and O-methyl O-(2,4,5-trichlorophenyl) ethylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1966
1966
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…Similar results were obtained in studies of the pick up of insecticide by Sitophilus granarius (Gowers & Le Patourel, 1984); and with Anopheles stephensi (Hadaway et al, 1970). Hadaway & Barlow (1963) found that the optimal particle size for transfer of dust particles to mosquitoes from a plywood surface was 20--40/~m. Our results indicate that sizes of 0.5-63/~m on ceramic and plastic surfaces, and of 0.5-7.5 #m on plywood are picked up most efficiently by the German cockroach.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar results were obtained in studies of the pick up of insecticide by Sitophilus granarius (Gowers & Le Patourel, 1984); and with Anopheles stephensi (Hadaway et al, 1970). Hadaway & Barlow (1963) found that the optimal particle size for transfer of dust particles to mosquitoes from a plywood surface was 20--40/~m. Our results indicate that sizes of 0.5-63/~m on ceramic and plastic surfaces, and of 0.5-7.5 #m on plywood are picked up most efficiently by the German cockroach.…”
Section: Discussionsupporting
confidence: 77%
“…The particle size of a dust may influence its insecticidal properties in several ways according to the nature of its action on the insect (David & Gardiner, 1950). Small particles may be better able to work their way into interstices between articulated members (intersegmental joints, or between legs and body) (Busvine, 1971) or to penetrate the cuticle (Armstrong et al, 1951;Hadaway & Barlow, 1963). The entry of dust into spiracles is also dependent on dust size, thus Hamilton (1937) found that particles up to 53/~m could enter all the spiracles of a locust and even particles as large as 104 #m could enter large spiracles.…”
Section: Introductionmentioning
confidence: 99%
“…In different epidemiological settings, this insecticide provided effective control for longer than 6 mo (Nasir et al 1982, WHO 2007, NЈGuessan et al 2009, NЈGuessan and Rowland 2012. Organophosphates and carbamates rapidily lose effectiveness on porous surfaces such as mud but provide persistent control on less porous substrates (Hadaway and Barlow 1963). ACTELLIC 300 CS showed a longer residual efÞcacy on cement walls compared with mud surfaces against a susceptible Kisumu strain of An.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that malaria mosquitoes may not follow the general temperature-toxicity rules. The second study [19] saw a negative TC for DDT and a positive TC for the organophosphate diazinon when An. stephensi was exposed to insecticide residues between 20 and 30°C.…”
Section: Susceptible Mosquitoes Could Be More Resistant During Coolermentioning
confidence: 98%